INTERPRETASI ELITE PENDIDIKAN INDONESIA TENTANG KURIKULUM PENDIDIKAN DASAR - Karti Soeharto, (Pendidikan Dasar, 2010)
Abstract; This research focuses on how the policy makers in the Indonesian Education interpret the components of basic education found in the statute No 20, 2003 concerning the National Education System. The sources of data are the Statute texts and the interview transcripts involving 10 participants. After analysing the data using Strauss and Corbin model, it is found out that the foundation of the basic education curriculum 1) comprises values and potential development and thus 2) it is under either the conservative or liberal ideology.